Analysis of the Quality of Healthcare Services in the Emergency Department of Permata Hati Hospital, Asahan Regency, 2026 - Dewi Ramayani; Rahmad Gurusinga; Sri Melda Br Bangun (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
The Emergency Department (ED) is an essential unit within hospital services that plays a crucial role in handling patients experiencing emergency situations. The quality of care provided in the ED greatly influences patient safety, the satisfaction of patients’ families, and the overall reputation of the hospital. This study aimed to examine the quality of healthcare services in the Emergency Department of Permata Hati Hospital, Asahan Regency, in 2026 by applying the five SERVQUAL dimensions, namely tangible, reliability, responsiveness, assurance, and empathy. This research used a quantitative method with a cross-sectional study design. The population consisted of family members who accompanied patients in the Emergency Department of Permata Hati Hospital during the research period. A sample of 97 respondents was obtained through probability sampling using an accidental sampling technique. Data collection was conducted using a structured questionnaire, and the data were analyzed using univariate analysis, bivariate analysis with the chi-square test, and multivariate analysis through logistic regression. The findings indicated that the majority of respondents considered the quality of healthcare services in the Emergency Department to be good. The bivariate analysis showed that reliability, responsiveness, assurance, and empathy were significantly associated with the quality of healthcare services, while the tangible dimension did not demonstrate a significant relationship. Furthermore, the multivariate analysis identified responsiveness as the most influential factor affecting the quality of healthcare services in the Emergency Department. In summary, the quality of healthcare services in the Emergency Department of Permata Hati Hospital is determined by several dimensions of service quality, particularly the responsiveness of healthcare professionals. Therefore, hospital management is encouraged to improve service responsiveness, strengthen effective communication, and foster empathetic attitudes among healthcare staff in order to continuously enhance the quality of emergency care services.